Characterising negative mental imagery in adolescent social anxiety - Chiu, K; Clark, DM; Leigh, E (Springer Nature, 2022)
Background Understanding the role of self-imagery in the development of social anxiety in adolescence holds promise for improving intervention. Cross-sectional studies indicate that imagery characteristics are associated with social anxiety symptoms, however, prospective studies are lacking. The current study examined concurrent and prospective associations between two image characteristics, namely observer-perspective and vividness, with social anxiety symptoms in a community adolescent sample (N = 616; 53% girls; aged 11–15 years). In addition, we examined common themes in the negative social anxiety-related images.